2010
DOI: 10.1186/ar3195
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in rheumatoid arthritis: prevalence, determinants and associations with disease activity and disability

Abstract: IntroductionThe aim of this study was to estimate the prevalence and determinants of vitamin D deficiency in patients with rheumatoid arthritis (RA) as compared to healthy controls and to analyze the association between 25-hydroxyvitamin D (25(OH)D) with disease activity and disability.MethodsThe study includes 1,191 consecutive RA patients (85% women) and 1,019 controls, not on vitamin D supplements, from 22 Italian rheumatology centres. Together with parameters of disease activity, functional impairment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
127
5
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(158 citation statements)
references
References 23 publications
19
127
5
7
Order By: Relevance
“…30%, P = 0.006) in patient group than healthy controls. [23][24][25] Low vitamin D3 levels may be associated with higher incidence of RA, as has already been mentioned by Song, et al 26 Other research done in India 27 which the result was against my research results, Thirty-one patients had high disease activity (DAS-28 score>5.1), 32 patients had moderate disease activity (DAS28 score 3.2-5.1) and 17 patients had low disease activity (DAS-28 score <3.2). Vitamin D3 level in high disease activity group was significantly low compared to…”
Section: Resultsmentioning
confidence: 97%
“…30%, P = 0.006) in patient group than healthy controls. [23][24][25] Low vitamin D3 levels may be associated with higher incidence of RA, as has already been mentioned by Song, et al 26 Other research done in India 27 which the result was against my research results, Thirty-one patients had high disease activity (DAS-28 score>5.1), 32 patients had moderate disease activity (DAS28 score 3.2-5.1) and 17 patients had low disease activity (DAS-28 score <3.2). Vitamin D3 level in high disease activity group was significantly low compared to…”
Section: Resultsmentioning
confidence: 97%
“…[22] who studied a comparable number of Egyptian SLE patients (40 SLE patients and 20 age and sex matched controls) and did not find significant correlation between vitamin D level and age or disease duration. And another study by Rossini et al [23] conducted on rheumatoid arthritis patients did not find an association between vitamin D level and disease duration. Also Dias de Castro et al [24] in their study on patients with Inflammatory Bowel Disease found no correlation between vitamin D and age or disease duration.…”
mentioning
confidence: 91%
“…The questionnaire we used (Table 1) has been validated in an Italian population. 4 It is a questionnaire easy to use and fast. A score below 7 was indicative of inadequate calcium intake (<1000 mg/die) via the diet.…”
Section: Methodsmentioning
confidence: 99%